Evaluasi Program Kemitraan dan Bina Lingkungan (PKBL) PT. Perkebunan Nusantara VII (Persero) Di Provinsi Lampung - Veronika Saptarini (e-JKPP, 2018)
ABSTRACT This article was written to assess implementation of Partnership and Environment Development Program undertaken by State-Owned Enterprises (SOEs) in Lampung Province, as sugestion and consideration for the company and its stakeholders, including the government to develop the benefits of the program. This research was conducted at PT. Perkebunan Nusantara VII, Ltd. The method used is the evaluative research method, with the evaluation model of Context, Input, Process, Product (CIPP). Results of the implementation of the Partnership and Community Development Program in PT. Perkebunan Nusantara VII, Ltd has a lot of impact that has been felt by the company and public program beneficiaries, but have not felt up by local government. Furthermore, although the company received numerous awards related to CSR and obtain performance assessment in the AAA category, but the company still faces a conflict with the community.